A Novel High‐Pressure Tin Oxynitride Sn2N2O. Issue 10 (22nd January 2020) - Bhat, Shrikant; Wiehl, Leonore; Haseen, Shariq; Kroll, Peter; Glazyrin, Konstantin; Gollé‐Leidreiter, Philipp; Kolb, Ute; Farla, Robert; Tseng, Jo‐Chi; Ionescu, Emanuel; Katsura, Tomoo; Riedel, Ralf
Abstract: We report the first oxynitride of tin, Sn2 N2 O (SNO), exhibiting a Rh2 S3 ‐type crystal structure with space group Pbcn . All Sn atoms are in six‐fold coordination, in contrast to Si in silicon oxynitride (Si2 N2 O) and Ge in the isostructural germanium oxynitride (Ge2 N2 O), which appear in four‐fold coordination. SNO was synthesized at 20 GPa and 1200–1500 °C in a large volume press. The recovered samples were characterized by synchrotron powder X‐ray diffraction and single‐crystal electron diffraction in the TEM using the automated diffraction tomography (ADT) technique. The isothermal bulk modulus was determined as B o =193(5) GPa by using in‐situ synchrotron X‐ray diffraction in a diamond anvil cell. The structure model is supported by DFT calculations. The enthalpy of formation, the bulk modulus, and the band structure have been calculated. Abstract : Tin hits six : High‐pressure synthesis of the first tin oxynitride Sn2 N2 O (SNO) is reported. All "Sn" atoms are in six‐fold coordination, showing a Rh2 S3 ‐type crystal structure with space group Pbcn . The results were also confirmed by DFT calculations (see figure).